Analisis Supervisi Klinis dalam Meningkatkan Mutu Pembelajaran di MI Sunan Kalijogo Malang - Moza Jauharotul Maknunah; Risfa Shofia; Muhammad Thaif Nur Abdillah; Shobihatul Fitroh Noviyanti (Al-Kindi, 2026)
This article discusses the results of clinical supervision analysis at MI Sunan Kalijogo, Karangbesuki, Sukun, Malang, which aims to determine the implementation of clinical supervision in improving the quality of learning. This analysis was conducted using qualitative research methods with observation, interviews, and documentation approaches. Data were obtained through direct observation of the clinical supervision process at MI Sunan Kalijogo as well as interviews with the principal and supervised teachers. The results show that clinical supervision at MI Sunan Kalijogo is implemented through three stages: planning, implementation of learning observations, and evaluation and follow-up. In the planning stage, the principal coordinates with teachers regarding learning tools and aspects to be observed. In the implementation stage, supervisors observe classroom learning activities to identify the strengths and obstacles faced by teachers during the teaching and learning process. Furthermore, in the evaluation and follow-up stage, a joint discussion is held to evaluate, provide input, motivation, and solutions to learning problems. The implementation of clinical supervision has a positive impact on improving teacher competence, especially in classroom management, the use of learning methods, and interaction with students. However, the implementation of clinical supervision still faces challenges, such as inadequate use of learning media and a lack of interaction between some teachers and students. Therefore, clinical supervision needs to be carried out continuously to ensure the quality of learning in madrasas continues to improve.